ChemInform Abstract: Palladium(II) Complexes Containing ONO Tridentate Hydrazone for Suzuki—Miyaura Coupling of Aryl Chlorides in Aqueous‐Organic Media. Issue 49 (December 2015) - Arumugam, Vignesh; Kaminsky, Werner; Bhuvanesh, Nattamai S. P.; Nallasamy, Dharmaraj
Abstract: The title complexes are highly active with 0.01 mol% loading and can be used for 5 cycles without significant loss of the activity.